Design for reading: an issue of conduct - Farbiarz, Jackeline Lima; Farbiarz, Alexandre (InfoDesign, 2006)
Design, as a field with inter-disciplinary vocation, appraises both the existence of knowledge formative units and the assessment of different performance areas. From this perspective, before executing job interventions, a designer should undertake a responsibility higher than merely knowing his specific instruction guidelines, i.e., observe, get acquainted to, and participate of knowledge fields which may be different from his own. However, sometimes market’s structure turns a consistent intervention unattainable, i.e., an intervention grounded both on his instruction specific guidelines and on the field’s reality, for which his performance is being needed. At other moments, the designer has a limited knowledge of the field in which he will perform the intervention, and this may cause the intervention to be impossible and/or contribute to generate social prejudice. This paper aims to discuss the designer performance in the educational field, analysing its contribution to the development of didactic and para-didactic material related to reading. We emphasize the double role of the designer’s skills and information which, sometimes due to an impossibility otherwise to unawareness, may lead him to the generation of social prejudice and to the lack of informative content.